Effectiveness of a rapid soil incubation method for determining potential acidity of soils in Rio Grande do Sul, Brazil - Gustavo Brunetto; Rodrigo Otávio Schneider Souza; Rogério Piccin; Roque Junior Sartori Bellinaso; João Kaminski; Carlos Alberto Ceretta; Lincon Stefanello; Rodrigo Krammes; Jacson Hindersmann; Luciano Colpo Gatiboni (Ciência Rural, 2019)
ABSTRACT: Potential soil acidity can be measured by two methods in the states of Rio Grande do Sul (RS) and Santa Catarina (SC): solution SMP or solution TSM (Buffer Santa Maria). Calibration of these methods is done by incubating soils for long periods (180 days) of CaCO3. The hypothesis of this study is that it is possible to reduce the incubation period in soils by using a soluble base such as calcium hydroxide. The study aimed to estimate potential acidity in a group of soils by moist incubation with Ca(OH)2 (short) as an alternative to the typical method with CaCO3 (long) and relate to the values estimated by the equation used by the Soil Chemistry and Fertility Commission of Rio Grande do Sul and Santa Catarina (CQFS-RS/SC; 2016). Ten soils with sandy texture and low organic matter content were collected at 0-20cm in the Campanha Gaúcha region of the state of RS and incubated for 180 days with doses of CaCO3 equivalent to 0, 25, 50, 75, 100, 125 and 150% of the lime requirement estimated by the solution TSM to raise to pH 6.0. Soils were also incubated for 4 days in an oven at 35ºC with 0.22mol L-1 Ca(OH)2 at doses equivalent to CaCO3. Short incubation of the soil with Ca(OH)2 may substitute long incubation with CaCO3. Also, estimating potential acidity using the equation of the CQFS-RS/SC (2016) overestimated potential acidity in soils with solution TSM pH values lower than 6.0 in this study.